Understanding the experience of shame in students within a South African university setting: a mixed methods psychosocial approach - Neel, Sheryl (My University, 2021)
Despite calls for more focus on affective processes at university, shame continues to be an overlooked emotion in higher education institutions and in the student experience research both globally and in South Africa. While there is a growing recognition in the psychoanalytic literature that learning environments fuel shame, there is unfortunately little work beyond the clinical realm. In education research, there has been an increasing acceptance of the profound impact that contentious contextual issues have on students’ university journeys. Students and classrooms are currently understood to exist within educational institutions that are situated within particular sociohistorical systems. The challenge is now to understand the reciprocal influences of these affective processes and social contexts on student experience and to develop more sophisticated frameworks to understand student engagement. Accordingly, this mixed methods study aimed to explore how shame shapes the student experience at the University of the Witwatersrand through interactions between micro-level shame dynamics (incorporating unconscious intersubjectivity) and meso and macro-level structures and their respective ideologies. Three data sets were collected – 472 surveys, 265 short shame stories, and ten in-depth interviews. The Shame Inventory scale was used to determine the prevalence and gravity of shame in the sample and common shame triggers. A psychosocial narrative analysis was conducted on the narrative data to interpret how and why students employed particular discourses – including unconscious shame coping scripts – to construct multiple student subjectivities. Drawing on object relations theory and principles from the theory of the stratification of emotions, this study illustrates that students’ complex intersubjective relationship to the educational institutional domain is central to an understanding of student shame. Results revealed student shame to be constructed as in compatible ideas of the self related to achievement, recognition and attachment at university. Shame emerged in the gap between the imagined and hoped for self and the struggling, rejected self, and appeared to be influenced by the unprecedented aspirational value of higher education, the power of the institution and peer group to sanction, and shame legacies rooted in racial and class stratification. Exposure of incompatible ideas of the ‘self’ was both a personal experience – driven by imaginative internalisation – and social, constructed through seven shame triggers identified as commonly occurring in the university context. Shame moves and countermoves were used to defend against multiple negative student identities. The findings illustrate how the confluence of micro, meso and macro social influences both produced and constrained shame resulting in a conflicted intermediate area of experience characterised by (mis)recognition, (mis)attunement, and (dis)engagement. Conflicted student positions were markers of the signal function of shame that can be used to understand how to disrupt psychosocial shame cycles in university contexts. This knowledge contributes to psychosocial accounts of how shame shapes the educational domain
A thesis submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Doctor of Philosophy in the field of Psychology, 2021